Penerapan Metode TOPSIS Dalam Sistem Pendukung Keputusan Seleksi Penerimaan Asisten Dosen Berbasis Web - Richard William Kho; Hindriyanto Dwi Purnomo (Universitas Budi Darma, 2023)
Technological developments in the field of education in tertiary institutions help and facilitate students in carrying out lecture processes such as conducting online classes, making it easy to obtain material provided by lecturers and various administrative processes that can be taken care of online. In the classroom, lecturers in teaching need teaching assistants as companions so that one of the success factors in the lecture process is based on the interaction between teaching assistants and students where the teaching assistant acts as a liaison between students and lecturers. At the Faculty of Information Technology, Satya Wacana Christian University, Informatics Engineering Study Program, to register as a teaching assistant, various processes are needed to meet the criteria that help in the selection process for teaching assistants, but in the selection process for accepting teaching assistants, it is still influenced by personal preferences which causes injustice in assessment and decision making. , various selection processes are complicated and time-consuming due to the many criteria with different levels of importance, the selection process is still done manually so that the selection process for hiring assistant lecturers is not effective and efficient. And in the process of storing data that is also ineffective, it is possible that it can be damaged or deleted. By using a decision support system and the TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution) it can assist in calculating all criteria simultaneously and giving weight to each criterion so that criteria can be identified that have more influence on the selection process and produce mathematical calculations so that the results which can be determined at the best value. The purpose of this study is to speed up the process of selecting teaching assistants by implementing the TOPSIS method to assist in selecting admission assistant lecturers. The results obtained are websites using the PHP programming language, Laravel framework, Bootstrap framework and MySQL database which are running well and have an attractive appearance. black box testing, validation of manual calculations where the results of the calculations are in accordance with the results on the website made with brandon which gets the highest prevalence value of 0.58.